Spotlight on corneal neurotization. (4th May 2021) - Giannaccare, Giuseppe; Pellegrini, Marco; Bolognesi, Federico; Fogagnolo, Paolo; Lupardi, Enrico; Allevi, Fabiana; Bernabei, Federico; Lozza, Alessandro; Plazza, Christian; Marchetti, Claudio; Scorcia, Vincenzo; Biglioli, Federico
ABSTRACT: Introduction : Neurotrophic keratopathy (NK) is a degenerative corneal disease originating from a damage to the trigeminal innervation. Corneal neurotization (CN) is a recently introduced surgical procedure consisting of the transfer of normally functioning nerves into the anesthetic cornea. Two main approaches are feasible: i) direct nerve transfer of a healthy nerve branch; ii) interpositional nerve graft coapted to a healthy donor nerve. Areas Covered : In this review, we present an overview of the current literature on CN for the treatment of NK. We discuss all the surgical approaches with specific advantages and disadvantages for each technique along with the results of published clinical studies in terms of both efficacy and safety. Expert Opinion : CN is a safe and effective treatment for NK. This procedure has shown the ability to improve corneal sensitivity, epithelial integrity, and visual acuity. Postoperative corneal re-innervation has also been detected by in vivo confocal microscopy. To date, no conclusive data are available about the technique of choice. In our practice, we perform direct nerve transfer techniques in patients with severe NK in order to take advantage of the presumed immediate sprouting from the transferred nerves; in the other cases, we use interpositional sural nerve graft.